Lex Publilia de cereis: римский закон в контексте войны - Квашин, В. А. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryV. Kvashnin. Lex Publilia de Cereis: Roman Law In the Context of WarThe article is devoted the “unknown” law of the Hannibalic War time, namely lex Publilia de cereis is analyzed. Both in Russian-speaking and world special literature the law isn’t investigated almost. Obviously it’s connected with a lack of the information in sources. The unique mention contains in work of Macrobius. The problem of authorship and time of pass of lex Publilia de cereis is examines in the article. The basic attention is payed to the maintenance and the purposes of the law.Key words: the history of Ancient Rome, Roman law, war with Hannibal, ancient tradition, religion.